The moderating effect between strengths and placement on children's needs in out-of-home care: A follow-up study. (January 2016) - Sim, Faye; Li, Dongdong; Chu, Chi Meng
Abstract: The negative impact of childhood maltreatment, which can often extend well into adulthood, consistently appears to be ameliorated if victimized children possess several resiliencies or strengths. However, little is known about how vulnerable children's outcomes are affected by different levels of strengths across different out-of-home placement settings. Hence, this study examined the association of two factors — children's strengths and placement type, with outcomes at two time-points during out-of-home care. The Child and Adolescent Needs and Strengths (CANS) tool was used to assess the outcomes of 285 children placed in residential homes or foster care in Singapore. Multiple regressions were conducted on CANS domain scores to evaluate whether level of baseline strengths and placement type predicted outcomes at two time-points after controlling for race, prior placements, age, gender, interpersonal trauma, and baseline needs scores. Results indicate that relative to residential care, foster care children are reported to be younger, with lower baseline needs, more prior placements, fewer baseline strengths and suffered fewer types of interpersonal trauma. After controlling for covariates, higher baseline strengths significantly predicted lower baseline needs of children across 3 of 4 CANS domains, regardless of placement settings. However, at reassessment 1 year later, there were significant interactions between strengths and placement type, whereby baseline strengths significantly predicted lower life functioning needs only in foster care. To conclude, in both residential and foster care, the protective effects of high strengths against child maltreatment were similarly apparent at baseline, despite clear differences in children's profiles across placement types. Over time, these initial benefits appeared to persist somewhat for children in foster care but seemed to diminish in more restrictive, residential settings and this warrants further investigation on children with more similar profiles. Nonetheless, it is clear that the continual development of children's strengths should be prioritized in case planning. Highlights: Foster children have fewer needs, strengths and trauma than those in group homes. At baseline, children with higher number of strengths have lower overall needs. Higher baseline strengths predict lower needs for fostered children after 1 year.